Pengaruh Penerapan Sistem Pengendalian Manajemen terhadap Kinerja pada Instalasi Rawat Inap di RSUD Kota Bandung - Utomo, Leksono Putro Hadi (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2010)
"This research is aimed to know the influences of management control system implementation towards performance of inpatient installations ath RSUD Bandung. The method used in this research is survey method, so that the information was collected from respondents by using questionnaires/survey which are distributed to finance and programs unit and inpatient units of RSUD Bandung. Sampling technique that used for this research is non probability sampling with the satisfied sampling technique. Obtaining this sampling technique based on the sample source from the entire population numbering 25 people, so this research is also a population research.Based on the hypothesis testing, it is known that there are positive and strong correlation for about 0.708pts between management control system implementation and the performance of inpatient installation in RSUD Bandung, and with the determination of 50.25%. this indicated that the management control system implementation has an influence on performance of inpatient installation in 50.25% and 49.75% for the rest influenced by another factors which not elaborated in this research."